In silico analyses of neuropeptide-like protein (NLP) profiles in parasitic nematodes. Issue 1 (January 2022) - McKay, Fiona M.; McCoy, Ciaran J.; Crooks, Bethany; Marks, Nikki J.; Maule, Aaron G.; Atkinson, Louise E.; Mousley, Angela
Graphical abstract: Highlights: Parasites possess a reduced complement of Caenorhabditis elegans neuropeptide-like protein (NLP)-encoding genes. Parasite NLP profiles are broadly conserved between nematode clades. Five NLP-encoding genes are completely conserved in the nine parasitic nematodes examined. Fourteen novel nematode NLP encoding genes are identified. Several highly conserved NLPs are bioactive. Abstract: Nematode parasite infections cause disease in humans and animals and threaten global food security by reducing productivity in livestock and crop farming. The escalation of anthelmintic resistance in economically important nematode parasites underscores the need for the identification of novel drug targets in these worms. Nematode neuropeptide signalling is an attractive system for chemotherapeutic exploitation, with neuropeptide G-protein coupled receptors (NP-GPCRs) representing the lead targets. In order to successfully validate NP-GPCRs for parasite control it is necessary to characterise their function and importance to nematode biology. This can be aided through identification of receptor activating ligand(s) via deorphanisation. Such efforts require the identification of all neuropeptide ligands within parasites. Here we mined the genomes of nine therapeutically relevant pathogenic nematodes to characterise the neuropeptide-like protein complements and demonstrate that: (i) parasitic nematodes possess a reduced complement of neuropeptide-like protein-encoding genes relative to Caenorhabditis elegans ; (ii) parasite neuropeptide-like protein profiles are broadly conserved between nematode clades; (iii) five Ce-nlps are completely conserved across the nematode species examined; (iv) the extent and position of neuropeptide-like protein-motif conservation is variable; (v) novel RPamide-encoding genes are present in parasitic nematodes; (vi) novel Allatostatin-C-like peptide encoding genes are present in both C. elegans and parasitic nematodes; (vii) novel neuropeptide-like protein families are absent in C. elegans ; and (viii) highly conserved nematode neuropeptide-like proteins are bioactive. These data highlight the complexity of nematode neuropeptide-like proteins and reveal the need for nomenclature revision in this diverse neuropeptide family. The identification of neuropeptide-like protein ligands, and characterisation of those with functional relevance, advance our understanding of neuropeptide signalling to support exploitation of the neuropeptidergic system as an anthelmintic target.